Addition Of Jackfruit Seed Ethanol Extract (Artocarpus heterophyllus L.) and Zinc Oxide to SPF Cream - Siti Muliani Julianty; Muflihah Fujiko; An Nisaul Faaizah (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Excessive exposure to ultraviolet radiation can trigger various skin disorders, including hyperpigmentation and an increased risk of skin cancer. The use of topical preparations with UV protection capabilities is one of the effective preventive measures. Skin protection efforts require effective sunscreen preparations, one of which is by utilizing natural antioxidants from jackfruit seeds (Artocarpus heterophyllus L.) combined with a physical filter Zinc Oxide (ZnO). Jackfruit seeds are known to contain flavonoid and phenolic compounds that have the ability to absorb UV rays. This study aims to examine the potential of utilizing natural ingredients combined with inorganic protective agents in increasing the protection factor value of sunscreen cream preparations. The study was conducted through the stages of plant identification, raw material processing, extraction using ethanol solvents, formulation of jackfruit seed ethanol extract cream with extract concentrations of 2.5%, 5% and 7.5%, and evaluation of the physical quality of the preparation. The parameters observed included organoleptic characteristics, homogeneity, emulsion type, pH, viscosity, irritation response in volunteers, and determination of the protection factor value against ultraviolet radiation using the Mansur method by measuring the absorbance of the preparations at a wavelength of 290–320 nm using a UV-Vis spectrophotometer. The results showed that all jackfruit seed ethanol extract cream formulas met the physical test requirements for topical preparations. All preparations had a stable pH in the range of 6.19–6.70, formed an oil-in-water emulsion system, and showed a viscosity that met quality requirements (2,300–13,660 cps). No irritation reactions were found in all volunteers. The protection factor values ​​for FI, FII, FIII, and FIV were 0.52308; 2.09996; 4.13436; and 6.60020, respectively. The formulation with the highest concentration showed the most optimal level of protection. These findings confirm the potential of these natural ingredients as effective and safe components in the development of sunscreen creams.